Sperm activation in nile tilapia oreochromis niloticus and effects of environmentally relevant pollutants on sperm fitness - Nadirah Musa (Tesis University of Stirling 2010, 2012)
In externally fertilizing fishes, multiple factors of the spawning environment may affect the sperm viability, and thus the fertilization rate. In this thesis, the sperm activation effect of osmolality of non-electrolytes and electrolytes activation media, pH and ion channel inhibitors on Nile tilapia, Oreochromis niloticus, and the effect of environmentally relevant pollutants (cadmium, malathion and rotenone) on sperm fitness (motility and morphology) were investigated.